Sustainable development in rainwater reuse: a proposal for dimensioning a tank at the UFVJM, Campus Mucuri (International Journal of Geoscience, Engineering and Technology, 2020)
Urbanization is an impact of great importance and relevance to society, but population growth, land occupation and climatic phenomena have exacerbated the challenges of water supply around the world. The use of rainwater for non-potable purposes is an alternative that can be adopted in regions where there is a poor distribution of rainfall per year. This work aims to study the sizing of rainwater reservoirs for non-potable purposes at the Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM), campus Mucuri. Therefore, a survey of data on the volume of abstraction was carried out, rainfall data and project characteristics were obtained. After obtaining the results, the choice of the 300 m³ reservoir volume was defined, since this volume shows the proximity between the Rippl and Simulation methods. The study on the use of rainwater for non-potable use (cleaning and irrigation) allowed the establishment of a water saving potential of 20%, meeting the expected annual demand, indicating that the implementation of this system is a viable alternative.